The effect of the age of cochlear implantation on the reading skills of children with hearing loss - Farzad Weisi; Mohammad Rezaei; Ayub Valadbeigi (Vesnu Publications, 2013)
Introduction: The significant effects of cochlear implantation on language, speech and reading skills become evident through the years following the implantation. The purpose of this study was to investigate the effects that the age at which cochlear implantation is performed has on reading skills progress. Materials and Methods: Participants were 24 children with cochlear implant from the second and the third grades of elementary education. They were all the residents of Tehran, Iran. Reading performance of the children was assessed by a recently-developed Persian tool called "Nama Reading Test". Results: Reading skills were significantly correlated with both the age of surgery and the duration of cochlear implant use (P < 0.05). Conclusion: Increased auditory input, provided by cochlear implant, improves language and reading skills. Therefore, it is necessary that implantation be performed as early as possible; long before the beginning of language acquisition. Keywords: Age of cochlear implantation, Reading skills, Children with hearing loss